Oral magnesium supplementation improves glycemic control in older Chinese adults with pre-diabetes and hypomagnesemia: a randomized controlled trial - Yang, Jingxin; Zhang, Huidi; Li, Yuting; Wu, Wenxuan; Pan, Min; Wang, Jingjing; Li, Guoxun; Wu, Ying; Guo, Chunlei; Yang, Lichen; Ding, Jing; Ding, Gangqiang (Frontiers in Nutrition, 2026)
PurposePre-diabetes significantly increases the risk of type 2 diabetes and cardiovascular disease. Magnesium deficiency is common and may contribute to dysglycemia. However, evidence for the efficacy of magnesium supplementation in pre-diabetes, especially in older adults with hypomagnesemia, remains limited and inconclusive. This exploratory trial aimed to evaluate the effects of oral magnesium supplementation on glycemic parameters and conducted exploratory metabolomic profiling in this population.MethodsIn this 4-month, randomized, double-blind, placebo-controlled trial, 71 community-dwelling older adults (mean age 68.7 ± 6.0 years) with pre-diabetes (fasting plasma glucose ≥5.6 mmol/L and/or HbA1c 5.7%−6.5%) and hypomagnesemia (plasma magnesium ≤ 0.80 mmol/L) were enrolled. Participants were randomly assigned to receive either magnesium oxide (360 mg elemental Mg/day) or an identical placebo once daily. The primary outcome was the change in fasting plasma glucose (FPG). Secondary outcomes included changes in insulin, HOMA-IR, HbA1c, glycated albumin, and inflammatory markers (hs-CRP, IL-6). Exploratory non-targeted metabolomic profiling was performed. Data were analyzed using ANCOVA adjusted for baseline values, following the intention-to-treat principle.ResultsSixty-five participants completed the trial. At baseline, the magnesium group had significantly higher insulin and HOMA-IR levels (both p < 0.05); analyses were adjusted accordingly. Compared to placebo, magnesium supplementation significantly increased plasma magnesium (adjusted mean difference: 0.056 mmol/L, 95% CI: 0.028 to 0.085; p < 0.001) and reduced FPG (adjusted mean difference: −0.497 mmol/L, 95% CI: −0.818 to −0.176; p = 0.003). The reduction in HOMA-IR favored the magnesium group but was not statistically significant after adjustment (p = 0.296). No significant between-group differences were observed for HbA1c, insulin, C-peptide, glycated albumin, or inflammatory markers. Exploratory metabolomics revealed alterations in putatively identified metabolites, with pathway analysis suggesting involvement of lipid and insulin resistance-related pathways; these findings are considered hypothesis-generating.ConclusionIn older adults with pre-diabetes and hypomagnesemia, magnesium supplementation effectively corrected magnesium deficiency and reduced FPG, but did not improve other glycemic indices including HbA1c or insulin resistance. The clinical significance of the isolated FPG reduction remains uncertain. The metabolomic findings require validation. Larger, longer-term trials are needed to determine if magnesium supplementation can prevent diabetes in this population.Clinical trial registrationwww.chictr.org.cn, identifier: ChiCTR2100047666.